Acute transaminitis after initial days of starting haloperidol - Rami Gabriel; Todd Wojtanowicz; Reza Farokhpay; Robert Bota (Mental Illness)
Haloperidol is a first-generation antipsychotic butyrophenone that is lipophilic, readily absorbed, and extensively metabolized in the liver. The occurrence of elevated liver enzymes with haloperidol is reported to be 2.4% with cases generally occurring in the setting of chronic use. In this case, we present a patient who developed elevated liver enzymes 1-2 days after starting haloperidol treatment on two separate occasions and in the context of negative hepatic viral and autoimmune serology. Liver enzymes consistently had alanine transaminase > aspartate transaminase and peaked at 288 U/L prior to discontinuation of the medication. The patient was taken off haloperidol after serology resulted and clozapine regimen started. He was able to tolerate clozapine well with recovery of his transaminitis and psychiatric stabilization.